"A beacon-light to the oppressed of every land": James Connolly and the work of the working-class intellectual. Issue 4 (1st October 2016) - Kelly, Aaron
Abstract: This article seeks to defend James Connolly from attacks on both the Left and Right, particularly the charge that his legacy is nationalist delusion and fanaticism. The article argues that Connolly's politics and his engagement with Irish cultural politics demonstrate his commitment to human equality as both a right, but also a principle of human intelligence. The article addresses Connolly's status as a working-class intellectual with reference to how he challenges conventional hierarchies between the philosophers of Marxism and the proletarians who are the object of those deliberations. The article argues that from Connolly's thought and activism an anti-colonial Marxism emerges which might help explain the neo-imperialist world we find ourselves in today and provide a critique lacking in the collapsed teleological versions of orthodox Marxism. The relations between his Marxism and nationalism are explored, as are his play Under Which Flag? his poetry and songs.